(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Promoting diversity and inclusion in medical nursing and laboratory professions is essential for enhancing patient care, fostering innovation, and advancing health equity. This article explores the importance of diversity and inclusion in healthcare settings, identifies barriers to achieving equitable representation, and offers strategies for creating more inclusive work environments.